Interplay of management and environmental drivers shifts size structure of reef fish communities - Steven W. J. Canty; A. Justin Nowakowski; Courtney E. Cox; Abel Valdivia; Daniel M. Holstein; Benjamin Limer; Jonathan S. Lefcheck; Nicole Craig; Ian Drysdale; Ana Giro; Mélina Soto; Melanie McField (Global Change Biology, 2024)
Countries are expanding marine protected area (MPA) networks to mitigate fisheries declines and support marine biodiversity. However, MPA impact evaluations typically assess total fish biomass. Here, we examine how fish biomass disaggregated by adult and juvenile life stages responds to environmental drivers, including sea surface temperature (SST) anomalies and human footprint, and multiple management types at 139 reef sites in the Mesoamerican Reef (MAR) region. We found that total fish biomass generally appears stable across the region from 2006 to 2018, with limited rebuilding of fish stocks in MPAs. However, the metric of total fish biomass masked changes in fish community structure, with lower adult than juvenile fish biomass at northern sites, and adult:juvenile ratios closer to 1:1 at southern sites. These shifts were associated with different responses of juvenile and adult fish to environmental drivers and management. Juvenile fish biomass increased at sites with high larval connectivity and coral cover, whereas adult fish biomass decreased at sites with greater human footprint and SST anomalies. Adult fish biomass decreased primarily in Honduran general use zones, which suggests insufficient protection for adult fish in the southern MAR. There was a north–south gradient in management and environmental drivers, with lower coverage of fully protected areas and higher SST anomalies and coastal development in the south that together may undermine the maintenance of adult fish biomass in the southern MAR. Accounting for the interplay between environmental drivers and management in the design of MPAs is critical for increasing fish biomass across life history stages.